APPLICATION OF THE MAKE A MACTH MODEL IN LEARNING THE VALUE MATERIAL OF PPKn PANCASILA IN GRADE IV STUDENTS OF SD NEGERI 2 KARANG DAPO - Rizki Putri (Teaching and General Education Studies, 2025)
The low understanding of Pancasila values among elementary school students indicates that pupils require more engaging and interactive learning strategies. This study aims to find out how well the Make a Match learning model helps fourth-grade students at SD Negeri 2 Karang Dapo understand Pancasila values in their PPKn subjects. The underlying problem is the low understanding of students due to the lack of captivating learning media and interactive teaching methods. The method used was a pseudo-experiment with a one-group pre-test and post-test design. The research subjects consisted of 20 students in grade IV. The research instrument is in the form of a multiple-choice test to measure learning outcomes and an observation sheet to assess student activity. The results showed a significant increase in the average score of students, from 60 (pre-test) to 80 (post-test). In addition, 85% of students show high activity during learning. The application of the Make a Match model has been proven to be able to create a fun learning atmosphere, increase student participation, and facilitate understanding of Pancasila values. Thus, PPKn learning effectively employs this model to enhance student learning outcomes. Future research is recommended to examine the long-term effects of this model and its application in different subjects or educational levels to determine its broader effectiveness.